A rare association of not so rare symptoms. (24th May 2012) - Shivamurthy, VM; Sridhar, A; Houtman, P; Kinder, A
Abstract : A 13 year old boy presented to us with history of vomiting, dizziness, red eyes and lethargy. Within the next few days he was found to have unilateral sensori neural deafness. He was also found to have anterior uveitis which as the disease progressed turned out to be interstitial keratitis. He was extensively investigated for infectious, inflammatory, rheumatological and autoimmune diseases, but all came back as negative. He was started on steroids after discussion with a tertiary rheumatology centre, to which he responded well. He was steroid dependant, so was commenced on methotrexate. His deafness completely resolved and his vision was better whilst on methotrexate. He was diagnosed to have Cogan syndrome based on the association of audio vestibular symptoms and interstitial keratitis and after excluding other conditions. Cogan syndrome is a rare disorder characterised by association of audio vestibular and ocular symptoms particularly interstitial keratitis. There is no diagnostic test as a result of which the diagnosis may be delayed. The disease may also be associated with non-specific systemic symptoms. The ocular symptoms typically may present as interstitial keratitis but in some cases it may present as uveitis or iritis and eventually progress to interstitial keratitis. Steroids and methotrexate are used in the treatment of the disease. If the condition is not diagnosed early and treated promptly it can cause permanent damage such as hearing loss and vision loss. Key message: Cogan syndrome is characterised by audio vestibular and ocular symptoms. One has to think of Cogan syndrome as a possibility when there is such an association. As there is no diagnostic test, there may be delay in diagnosing the disease. But early detection and treatment may prevent the permanent damage such as hearing loss or loss of vision.